ANALISIS PENGUNGKAPAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) PT. GAS NEGARA Tbk. TAHUN 2016-2020 BERDASARKAN STANDAR GLOBAL REPORTING INITIATIVE (GRI) - Wilkinson Mardika; Faisal Faisal (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to analyze the disclosure of the Sustainable Development Goals as reflected in the PT Perusahaan Gas Negara Tbk Sustainability Report based on the GRI Standards for the 2016-2020 period. This type of research is qualitative research. The research method used is the Content Analysis method. The data collection technique used is documentation, collecting relevant data and information sourced from literature studies and internet searching in order to obtain information that can be useful for conducting research. The conclusion based on the results of the study shows that based on the rankings in Table 3.2, the Suistainability Reporting Disclosure Predicate in the 2016 period is categorized as uninformative with an average value of 28% from data processing, in the 2017 period it is categorized as uninformative with an average value of 39% from data processing. , in the 2018 period it is also still categorized as uninformative with an average value of 39% data processing. Meanwhile, in the 2019 period, it was categorized as less informative with an average value of 52% from data processing. For the 2020 period, it can be categorized as informative with an average value of 71% of data processing. In the report found inaccuracies in some of the disclosures reported. It is hoped that PT Perusahaan Gas Negara Tbk will report more fully, especially related to specific topics such as economic, environmental, and social topics in order to be better in the future.